Heterogeneity in Hyporheic Flow, Pore Water Chemistry, and Microbial Community Composition in an Alpine Streambed. Issue 11 (20th November 2019) - Nelson, Amelia R.; Sawyer, Audrey H.; Gabor, Rachel S.; Saup, Casey M.; Bryant, Savannah R.; Harris, Kira D.; Briggs, Martin A.; Williams, Kenneth H.; Wilkins, Michael J.
Abstract: The hyporheic zone, where surface water and groundwater mix, is an important microbial habitat where biogeochemical reactions influence water quality. We show that spatial variability in hyporheic flow in the East River near Crested Butte, CO, drives heterogeneity in streambed geochemical conditions and microbial community assemblages, but the diversity of microbial assemblages remains nearly constant throughout the reach. In July 2018, we collected approximately 100 pore water samples at 20‐cm depth and analyzed them for anions, cations, dissolved organic carbon, dissolved organic matter (DOM) quality, and basic water quality parameters. Vertical hydraulic head gradients were also measured to assess the potential for upward or downward flow, and heat tracing was used to quantify vertical flux rates at a subset of locations. We found that regions of the streambed that are more groundwater‐dominated contain less dissolved oxygen, higher concentrations of reduced metals, and more microbially processed, recalcitrant DOM, while more surface water‐dominated locations contain higher dissolved oxygen concentrations and terrestrially derived, labile DOM. 16S rRNA gene sequencing of extracted DNA revealed that microbial community composition varies with geochemical gradients related to hyporheic flow. These findings provide a better understanding of hyporheic controls on streambed biogeochemistry during the baseflow season, which is expected to lengthen with climate change in alpine watersheds due to earlier snowmelt onset and reduced snowpack. Plain Language Summary: Groundwater and surface water mixing in streambeds (hyporheic exchange) is important for nutrient and carbon cycling and influences the overall quality of surface water. In this study, we aimed to map relationships between hyporheic exchange, pore water chemistry, and microbial communities in the streambed of an alpine river during low flow conditions. We found that regions of the streambed with greater surface water influence had larger concentrations of dissolved oxygen and microbially available carbon compounds. The composition of streambed microbial communities also shifted with changes in pore water chemistry, though communities were all similarly diverse. As climate change progresses, earlier snowmelt onset and reduced snowpack should alter flow and biogeochemical processes in streambeds. This study provides a baseline for exploring future changes in alpine streambeds. Key Points: Meander morphology influences patterns of recharge and discharge in the channel Intrameander flow paths affect source and lability of dissolved organic matter throughout the streambed Microbial assemblages shift with pore water chemistry, but diversity remains consistently high